The Foochow entrepreneurial characteristics : comparison between generations - Ernest Cyril, de Run; Malar, Subramaniam; Wong, Michael Sing Lung (Journal of Asia Entrepreneurship and Sustainability, 2006)
This study identifies the current motivation and entrepreneur characteristics of the second / third generation Foochow Chinese in Sarawak as compared to their forefathers. This is then compared to determine what has been lost or gained in the Foochow entrepreneurial spirit. Data was obtained through indepth interview of thirty Foochow entrepreneurs. The study utilizes Evolutionary Psychology Paradigm and is analyzed using frequency and Crosstabulation. The findings indicate specific generation based perception and motivators of entrepreneurship.